Gyeprestaurációs esélyek lehetőségek különböző élőhelyeken, eltérő állatokkal végzett legeltetés során.: Áttekintő esettanulmányok I: fás legelők, erdőirtások - Saláta, Dénes; Szentes, Szilárd; Kevi, Andrea; Balogh, Dániel; Turcsanyi-Jardi, Ildiko; Szabó-Szöllősi, Tünde; Wagenhoffer, Zsombor; Sipos, László; Salata-Falusi, Eszter; Stilling, Ferenc; Penksza, Péter; Fintha, Gabriella; et al. (Gyepgazdálkodási Közlemények, 2025)
Since 1992, data on the vegetation of the various grasslands in the country have been collected continuously and in recent years the vegetation of these areas has been surveyed repeatedly to monitor changes. Our aim has been to identify the conservation values and grassland management values of grasslands grazed by different animals, grasslands and wooded pastures that have been planted or restored. In the Pannonian region, we have also carried out studies in lowland mid-range, hilly areas. Areas grazed by horses, Hungarian grey cattle, sheep, goats and domestic water buffalo. The results of grazing with different animals at several study sites have been monitored and have been continuously monitored since 1994. In this paper, a brief overview of the results of the conversion of wooded pastures and deforested areas to pasture is presented. Results from three wooded pastures and one shrubland are summarised. Results from Hungarian grey cattle sheep and Hungarian domestic buffalo pasture are summarised. In all areas, grazing was successful in maintaining habitats. The maintenance of the scrub area and the preservation of its mosaicity were best ensured in the Hungarian grey cattle pasture. Sheep were responsible for maintaining the grassland vegetation. Water buffaloes ensured the maintenance of the pasture.